The Effect of Using a Combination of Sorbitol and Glycerol Plasticizers on the Characterization of Edible Film from Porang (Amorphophallus oncophyllus) Starch - Maghfirah, Awan; Sudiati, Sudiati; Br Sitepu, Silvya Nurrein K.; Widyanti, Meutia (Talenta Publisher, 2023)
Edible films present an eco-friendly alternative for food packaging compared to traditional plastic materials. This study investigates the effects of glycerol and sorbitol plasticizers on the properties of edible films. The research involves crafting these films using porang (Amorphophallus Oncophyllus) starch. Glycerol plasticizers were incorporated at a concentration of 100%, while sorbitol was utilized at varying levels (0%, 25%, 50%, 75%, 100%) to evaluate their impact on film characteristics. The films were produced using the melt intercalation method at a gelatinization temperature of 80Â°C and a firing temperature of 70Â°C. Notably, the most favorable physical test outcomes were observed with adding 100% sorbitol, including thickness, density, water absorption, and degradability improvements. Meanwhile, adding 25% sorbitol yielded the highest tensile strength and elongation values.